PENYELESAIAN SENGKETA ANGKUTAN LAUT BAGI PELAKU BISNIS. - Ludian Toro; Wisanggeni Bagus Anggoro; Brian Septiadi Daud (House of Management and Business (HOMBIS) Journal, 2022)
This article discusses the resolution of disputes experienced by sea freight service users if they experience problems when sending their business goods. This article uses a research method in the form of a literature study by collecting related articles on dispute resolution regarding sea transportation. from the existing conclusions, it can be concluded that the conclusion step taken by a businessman in resolving sea transportation disputes with sea transportation service providers is to use non-litigation channels, but if it is felt that the solution offered is not enough, a businessman can use litigation by bringing the dispute issue to the party. authorized, a businessman must also take into account the use of insurance to secure goods to be shipped using sea freight services.